Clinical Correlates of Early-Onset Hypertension - Suvila Karri; Lima Joao AC; Cheng Susan; Niiranen Teemu J (OXFORD UNIV PRESS, 2022)
BACKGROUND
Early-onset hypertension has been established as a heritable trait and a risk factor for cardiovascular disease outcomes. However, the clinical correlates of early-onset hypertension remain unidentified.
METHODS
In this study, we assessed the demographic characteristics and lifestyle factors related to hypertension onset age in a sample of 3,286 Coronary Artery Risk Development in Young Adults (CARDIA) study participants (mean baseline age 25 4 years, 57% women). We examined the association between the participants' baseline characteristics and age of hypertension onset subgroups (<35, 3544, or >= 45 years) using a multinomial logistic regression model with those who did not develop hypertension as the reference group. Hypertension onset was defined as blood pressure >= 140/90 mm Hg or antihypertensive medication use on 2 consecutively attended follow-up visits.
RESULTS
In the multinomial logistic regression model, individuals who were black (odds ratio [OR], 5.08; 95% confidence interval [CI], 3.17-8.14), were more obese (OR, 1.57; 95% CI, 1.32-1.88), or had higher total cholesterol (OR, 1.34; 95% CI, 1.13-1.60 per SD) had increased odds of early-onset hypertension (onset at <35 years) vs. not developing hypertension. In contrast, 1-SD higher high-density lipoprotein (HDL)-cholesterol was related to decreased odds of early-onset hypertension (OR, 0.71; 95% CI, 0.57-0.89). The odds for having earlier hypertension onset increased linearly across age of onset categories in black individuals and individuals with lower HDL-cholesterol (P < 0.05 for trend for both).
CONCLUSIONS
Our findings suggest that individuals who are black, obese, have higher total cholesterol, or have lower HDL-cholesterol level, are potentially at an increased risk of having early-onset hypertension.